Estudo da absorção do vapor de etanol, carregado por gás carbônico, em diferentes solventes - Cardoso, Valdemir Moretto (2015)
In Brazil, ethanol is produced from fermentation route, being a process well consolidated and largely used for decades in the production units without facing significant changes in its design. In order to increase the productivity in this process, few studies have evaluated ethanol recovery using CO2 to strip it from the vine of the fermentation stepwise and from the vine without yeasts. Thus, in the fermentation stepwise, there is a possibility of prolonging the yeast s activities, by maintaining the ethanol concentration below the inhibition limit of action of this type of organism for more time, causing a higher ethanol production in this step. Besides that, the stripped ethanol from the vine without yeast arises a san alternative to the first distillation step, impacting in a reduction of the energy consumption in the process due to the least necessity of water vapor use. Under these conditions, the generated gas would be mainly a mixture between CO2 gas and ethanol-water vapor. Because of this, it was proposed to evaluate the ethanol recovery in this gaseous mixture by absorption unit operation. Then, it was assembled a system containing a saturated gaseous mixture generation in ethanol, passing continuously in countercurrent flow with the recirculated liquid into a absorption column, before being released to the environment. Through recirculated liquid samples over time, it was possible to follow the effects caused of some absorbents indetermined concentrations and determined gaseous mixture and absorbent flows. As absorbents were evaluated aqueous solutions of ethylene glycol, diethylene glycol and glycerol. With the work results was possible to compare solute concentration over time in each absorbent, to measure the ethanol recovery level, to estimate the controller phase(gaseous or liquid) and to calculate the overall volumetric mass transfer coefficients of the liquid phase (KLa), proposing correlations for that and for the ethanol recovery level in the studied conditions. Ethanol concentration until 63% (w/w) and recovery values closer than90% were observed. Besides that, it was proposed a method to determine KLa and it were got and evaluated 24 equations to estimate it and more 22 in order to estimate the ethanol recovery level.